IT Risk Management based on ISO 31000 For BRImo Application (BRI Mobile) as an Transaction Processing Information System - Fatma Wati; Sarmila Sari; Joy Nashar Utamajaya (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
BRImo application is a software support system owned by Bank bri in order to increase profits and provide maximum service to customers. With the BRImo application, it can make it easier for customers to register for new account openings and e-banking transactions anywhere without being limited by space and time. However, implementing information technology is not without risk, because banks are a highly regulated industry and must be carried out prudently. With the growing complexity of BRI's business activities and operations, the risks faced are also getting bigger. Threats that arise to operational activities can be triggered by various factors, both internal and external. Therefore, there is a need for risk management analysis on the BRImo Application using the ISO 31000 framework so that the possible risks that will occur can be minimized or eliminated by carrying out Risk Assessment and Risk Treatment. The results of this study are various possible risks in the identified application using a probability and impact matrix as well as the handling of the possible risks that exist. So that the results of this risk analysis can be used to help companies prevent, minimize risks, and treat these risks according to their priorities before the possibility of these risks hampering the company's performance.